2022
DOI: 10.1097/wco.0000000000001084
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of sleep disorders in pre-Parkinsonian syndromes

Abstract: Purpose of reviewNeuroimaging has been advanced in the last years and enabled clinicians to evaluate sleep disorders, especially isolated rapid eye movement sleep disorder (iRBD), which can be seen in alpha-synucleinopathies. iRBD is the best prodromal clinical marker for phenoconversion to these neurodegenerative diseases. This review aims to provide an update on advanced neuroimaging biomarkers in iRBD.Recent findingsAdvanced structural MRI techniques, such as diffusion tensor imaging and functional MRI, neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Compared with previous review articles on this topic, we included many more eligible articles. Those reviews chose either to discuss neuroimaging findings in iRBD in general (including nuclear medicine or ultrasound techniques, drastically limiting the coverage of MRI anomalies) [5,[103][104][105][106][107][108] or simply not to cover new MRI techniques available nowadays (such as neuromelanin or spectrometry) [109,110]. Second, MEDLINE and Google Scholar are among the most used databases worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous review articles on this topic, we included many more eligible articles. Those reviews chose either to discuss neuroimaging findings in iRBD in general (including nuclear medicine or ultrasound techniques, drastically limiting the coverage of MRI anomalies) [5,[103][104][105][106][107][108] or simply not to cover new MRI techniques available nowadays (such as neuromelanin or spectrometry) [109,110]. Second, MEDLINE and Google Scholar are among the most used databases worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Functional MRI studies (f-MRI) showed altered connectivity not only within basal ganglia, but also in cortico-striatal and cortico-cortical networks. 60 …”
Section: Rem Sleep Behavior Disorder and Biomarkers For Phenoconversi...mentioning
confidence: 99%
“…Gaurav R and their research team further confirmed a decrease in both the volume and signal intensity of the SNpc in individuals with iRBD, emphasizing the role of NM‐MRI signal as a warning sign of SNpc neurodegeneration in parkinsonism (Gaurav et al, 2022). Thus, NM‐sensitive MRI examination of SNpc and LC holds promise as an imaging biomarker in the prodromal phase of PD (Mitchell et al, 2021; Ota et al, 2022).…”
Section: Introductionmentioning
confidence: 99%